[ASME recognized the Mechanical Engineering Program] - Mechanical Engineering Department - De La Salle Univerity, Manila (Animo Repository, 1997)
Efren dela Cruz, Acting Chair of the Mechanical Engineering Department, reported that the Mechanical Engineering Program of the University was recognized by the American Society of Mechanical Engineers (ASME) International.